Bio equivalence of Two Formulations of Daidzein Administered in a Single Dose to Healthy Chinese Volunteers - He, Jianchang; Gu, Shenghua; Zhang, Qing; Feng, Enfu; Li, Xingyi; Xu, Guili (Arzneimittelforschung, 2008)
In this two-treatment, two-period, randomized, crossover bioequivalence study of daidzein, which belongs to the isoflavone class of flavonoids and is classified as a phytoestrogen, two formulations (dripping pills, a rapidly-dissolvable formulation, and tablets) were compared in 20 healthy Chinese male subjects. The drug was given in a single dose of 50 mg and blood samples were withdrawn during 24 h after drug administration. Daidzein was separated and analyzed using a validated liquid chromatography – tandem mass spectrometry (LC-MS/MS) method. The pharmacokinetic parameters were determined from the plasma concentration-time profiles of both formulations. The primary calculated pharmacokinetic parameters were compared statistically to evaluate bioequivalence between the two preparations, using various statistical methods. The analysis of variance (ANOVA) did not show any significant difference between the two formulations and 90% confidence intervals fell within the acceptable range (80 – 120%) for bioequivalence. Based on these statistical inferences it can be concluded that the two formulations of daidzein are likely to be bioequivalent.
Keywords: Daidzein, bioequivalence, pharmacokinetics; Heart therapeutics; Isoflavones